Passive Heat Recovery System Using Combination of Heat Pipe and Thermoelectric Generator. (August 2015) - Remeli, M.F.; Verojporn, K.; Singh, B.; Kiatbodin, L.; Date, A.; Akbarzadeh, A.
Abstract: A different ways of waste heat recovery and conversion to electricity using a thermoelectric generator (TEG) assisted by heat pipes is introduced in this paper. The system consists of the TEG sandwiched between two heat pipes, one connected to the hot side of the TEG and the second one connected to the cold side of TEG. Experiments were conducted for a proof of concept of such system, and the experimental result was used to validate the theoretical model developed. It was found that both the experimental and the theoretical results share the same graphical trend in term of the rate of heat transfer and the effectiveness of heat exchanger. Further investigation in the theoretical model can narrow down the error.